THE APPLICABILITY OF ARTICLE 91 SUBSECTION (1) OF LAW NUMBER 28 OF 2009 ON REGIONAL TAXES AND LEVIES CONCERNING THE AUTHENTICITY OF A DEED - I Gede Edy Korneawan; Ni Luh Made Mahendrawati; I Nyoman Alit Puspadma (NOTARIIL Jurnal Kenotariatan, 2023)
The Law Number 28 of 2009 on Regional Taxes and Levies creates a conflict: Article 90 says taxes are due when the deed is signed, while Article 91 requires proof of tax payment before the deed can be signed by the Land Deed Official/Notary. This study aims to examine the requirements for drawing up an Authentic Deed in order to have a legal force as solid proof and to examine the legal protection for the community upon the enactment of Article 91 subsection (1) of Law Number 28 of 2009. This study is normative legal research using a statutory and conceptual approach. The legal materials are collected using the document study technique and analyzed using a descriptive method, legal interpretation, and argumentum per analogiam (Legal Analogy). The results of this study indicated that an Authentic Deed is a solid proof comprising head, body and closing of the deed. That deed shall provide certainty on the date of drawing up and signing the deed in order to provide legal certainty. The payment of the Duties on Acquisition of Rights on Land and/or Buildings is not a prerequisite for drawing up an Authentic Deed. The payment may be made after the Notary Deed is ratified and before it is registered to the Land Office by the Land Deed Official. If the Authentic Deed has not been signed or ratified by the Land Deed Official, the transfer of land rights would not happen as there is no written evidence which can protect the buyer.